Individual Differences in Decision Making Depend on Cognitive Abilities, Monitoring and Control. (3rd February 2016) - Jackson, Simon A.; Kleitman, Sabina; Stankov, Lazar; Howie, Pauline
Abstract: Decision making is the process by which actions are constructed and initiated. Across many research streams, this can be explained in terms of three broad cognitive processes: cognitive abilities that construct judgements and potential courses of action, and interacting monitoring and control processes that determine when to initiate them as behaviour. The aim of this research was to investigate the generality of individual differences in these processes, and their power to predict patterns of decision behaviour identified in our previous research. Undergraduate participants ( N  = 364) completed nine tests assessing cognitive abilities, monitoring confidence, control thresholds and various patterns of decision behaviour. The tests differed in their cognitive ability requirements and the nature of the payoffs associated with decisions. Cognitive abilities were a strong predictor of individuals' decision competence and optimality, while monitoring confidence and control thresholds were strong and unique predictors of their overall decisiveness, and reckless and hesitant errors. These results were strongest when the measures of cognitive abilities and monitoring confidence were derived from tests with the same cognitive requirements as the tests used to derive the decision behaviours and when the control threshold measure was derived from tests with the same decision payoffs as the test used to derive the decision behaviours. This effect was particularly pronounced for control thresholds, highlighting the domain‐specific nature of cognitive control processes. These findings demonstrate how cognitive abilities, monitoring output and control thresholds interact with cognitive requirements and context‐specific payoffs to drive individual differences in decision‐making behaviour. Copyright © 2016 John Wiley & Sons, Ltd.